Academic inclusion and wellbeing of immigrant youth in Portugal: The role of acculturation dynamics and perceived discrimination - Rodrigues, R. B.; Guerra, R.; Barreiros, J.; Carmona, M.; Aguiar, C.; Alexandre, J.; R. Costa-Lopes; Costa-Lopes, R. (Global Youth Mentoring Network - III International Conference: Youth mentoring, cultural diversity, minorities, and migrant groups, 2017)
In the last decades, Portuguese public schools have received a significant number of foreign children and young people. Despite the positive evolution of public policies towards the integration of immigrants, there are still educational inequalities between foreigners and nationals of foreign descent and Portuguese nationals. The present research examines the role of acculturation preferences (i.e., integration, assimilation, separation or marginalization) and perceived discrimination on foreign children’s school success and well-being. A total of 583 students attending the 4th, 5th and 6th grades participated in the study (229 foreign, 196 Portuguese of foreign descent and 168 Portuguese of Portuguese origin). The results show that foreign students prefer integration strategies (57.8%) and separation (20.5%), whereas Portuguese students prefer integration (55%) and marginalization (19%). The results also reveal a negative impact of perceived discrimination on both immigrant and foreign descent’s school success and well-being. The results confirm the persistence of significant challenges to the integration of children and young people with an immigrant background in schools in Portugal, and therefore call for the design and implementation of interventions to promote the integration of social diversity in educational settings.